Effect of Tween 80 and Span 80 Surfactants Systems on the Malus domestica Emulsions for Anti-Cutibacterium acnes - Handoyo, Theodorus Rexa; Resmi, Juniar Kalpika; Hutabarat, Rahmi; Guanse, Yovi (Sciences of Pharmacy, 2026)
Red apple (Malus domestica) extract, rich in hydrophobic quercetin, was formulated into oil-in-water (O/W) emulsion using a 22 factorial design to evaluate Tween 80 (8-10 g) and Span 80 (2-4 g) concentrations, targeting pH (4.5-6.0), transmittance (90-100%), and viscosity (10-2000 cPs). Design-Expert® 13 analysis identified formulations F1, FA, and FAB within acceptable physical property ranges, with all red apple emulsions exhibiting O/W type, skin-compatible pH (5.20-5.48), high transmittance, and suitable viscosity. Freeze-thaw cycling (3 cycles, -15/25°C) and centrifugation showed physical stability with non-significant changes for F1 (p > 0.05). The agar well diffusion assay was performed on F1 (n = 3), which exhibited optimal physical parameters and met stability criteria, revealing Cutibacterium acnes inhibition zones up to 22.7 ± 0.577 mm. Thus, F1 emerges as a promising nanoemulsion candidate demonstrating antibacterial activity against acne-causing bacteria.